Bumblebee diversity and pollination networks along the elevation gradient of Mount Olympus, Greece. Issue 11 (30th July 2020) - Minachilis, Konstantinos; Kantsa, Aphrodite; Devalez, Jelle; Trigas, Panayiotis; Tscheulin, Thomas; Petanidou, Theodora
Abstract: Aim: We studied bumblebee diversity and bumblebee pollination networks along the altitudinal gradient of Mt. Olympus, a legendary mountain in Central Greece, also known for its exceptional flora. Location: Mt. Olympus, Central Greece. Taxon: Bombus (Latreille, 1802). Methods: We explored 10 study sites located on the north‐eastern slope of the mountain, from 327 to 2, 596 m a. s. l. Bumblebee surveys were carried out on a monthly basis using pan traps (years 2013 and 2014) and random transect observations assisted by hand netting (years 2013, 2014, and 2016); visited flowering plants and their diversity were recorded during the transect observations. Results: With a total of 22 recorded bumblebee species and one species complex, Mt. Olympus is one of the richest mountains in Mediterranean Europe regarding bumblebee diversity. Bombus quadricolor was recorded as a new species for Greece, whereas four species were recorded at their southernmost distribution limit, therefore possibly vulnerable to climate change. Species richness of both bumblebees and plants in flower followed a unimodal pattern along the altitudinal gradient, the former peaking at high altitudes (1, 900–2, 200 m a.s.l.), the latter at lower to intermediate altitudes (500–1, 500 m a.s.l.). Bumblebee–plant visitation networks were larger, more diverse and more generalized in the between intermediate altitudes (1, 500–1, 800 m a.s.l.), while nestedness peaked at low and high altitudes. Main conclusions: Our results disclose the differential significance of the altitudinal zones of Mt. Olympus for the conservation of the diversity of bumblebees and their host plants, as well as of the interactions among them. Furthermore, they highlight the importance of this mountain, because of its South‐European location, regarding climate change impacts on the bumblebee fauna of Europe. All in all, they point towards more reinforced conservation measures to be taken including the expansion of the protection status to the entire mountain.